Etiology and Oral Antibiotic Susceptibility Patterns of the First Urinary Tract Infection Episode in Infants Under 6 Months of Age: A 17-Year, Retrospective, Single-Center Study in Italy - Francesca Bagnasco; Francesca Lorenzini Ceradelli; Alessio Mesini; Carolina Saffioti; Erica Ricci; Chiara Russo; Marcello Mariani; Elisabetta Ugolotti; Emanuela Caci; Debora Contu; Elisa Tavella; Alessia Cafaro; et al. (Microorganisms)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections in children, and the antibiotic susceptibility in the youngest patients remains poorly understood. This study aimed to describe the distribution of uropathogens and their antibiotic susceptibility, focusing on oral formulations. Methods: Data from the first microbiological isolation, between January 2007 and December 2023, at Istituto Gaslini, in young infants (aged <6 months), were analyzed. Results: We isolated 2473 infants’ first pathogen, with a median age in the sample of 2.8 months and 62.6% male. A total of 2498 bacterial isolates were identified, of which 88.8% were Gram-negative and 11.2% were Gram-positive. Escherichia coli (53%) was the most frequent isolate, followed by Klebsiella pneumoniae (12.3%) and Enterococcus spp. (9.6%). No significant differences were observed between males and females, but infants younger than 3 months exhibited a significantly different pathogen distribution compared to older infants. The pathogen distribution showed significant changes before and after 2015, with a marked increase in Klebsiella pneumoniae isolates post-2015. Escherichia coli showed increases in resistance to amoxicillin-clavulanate and ciprofloxacin after 2015. Conclusions: Escherichia coli remains the most common uropathogen; however, Klebsiella pneumoniae has not only shown a high prevalence but also significant resistance, particularly in recent years.